Chlorination of Amino Acids: Reaction Pathways and Reaction Rates - How, Zuo Tong; Linge, Kathryn; Busetti, Francesco; Joll, Cynthia (American Chemical Society, 2017)
Chlorination of amino acids can result in the formation of organic monochloramines or organic dichloramines, depending on the chlorine to amino acid ratio (Cl:AA). After formation, organic chloramines degrade into aldehydes, nitriles and N-chloraldimines. In this paper, the formation of organic chloramines from chlorination of lysine, tyrosine and valine were investigated. Chlorination of tyrosine and lysine demonstrated that the presence of a reactive secondary group can increase the Cl:AA ratio required for the formation of N,N-dichloramines, and potentially alter the reaction pathways between chlorine and amino acids, resulting in the formation of unexpected by-products. In a detailed investigation, we report rate constants for all reactions in the chlorination of valine, for the first time, using experimental results and modelling. At Cl:AA = 2.8, the chlorine was found to first react quickly with valine (5.4x104 M-1 s-1) to form N-monochlorovaline, with a slower subsequent reaction with N-monochlorovaline to form N,N-dichlorovaline (4.9x102 M-1 s-1), although some N-monochlorovaline degraded into isobutyraldehyde (1.0x10-4 s-1). The N,N-dichlorovaline then competitively degraded into isobutyronitrile (1.3x10-4 s-1) and N-chloroisobutyraldimine (1.2x10-4 s-1). In conventional drinking water disinfection, N-chloroisobutyraldimine can potentially be formed in concentrations higher than its odour threshold concentration, resulting in aesthetic challenges and an unknown health risk.